REX–K3L: A Novel Approach for Neuromimetic and Contextual Machine Logic - Fellouri, Abdelkrim; Adjailia, Meriem (International Journal of Scientific Research and Management (IJSRM), 2025)
This document presents REX–K3L, a new machine logic system designed to overcome the limitations of traditional binary logic in the face of increasing data complexity and AI demands. Inspired by biological and neural mechanisms, REX–K3L uses ternary logic (Active, Passive, Null) and a contextual "X" state to manage ambiguity.Its key innovations include a rotational memory mechanism that creates unique, time-dependent memory snapshots, enhancing security against cloning. It also introduces Lactal Crypto, a trit-based cryptographic model for secure communication and encoding.Preliminary simulations demonstrate its capability for adaptive signal processing and dynamic memory modeling. REX–K3L represents a step forward towards more context-aware and biologically inspired computing, where logic can evolve.